Ash formation characteristics in co-combusting coagulation sludge and Zhundong coal. (1st March 2022) - Zheng, Liangqian; Jin, Jing; Liu, Zhongyi; Kou, Xuesen; He, Xiang; Shen, Long
Highlights: A new way to convert solid waste to energy and mitigate Zhundong coal slagging in CFB. To quantify real-time influence of sludge on the ash fusion, ash shrinkage curve was applied. Ash fusion process of Zhundong coal was divided into two stages to explain fusion mechanism. New object is sludge treated by coagulants due to high environment standards recently. Ash formation characteristics consisted of ash fusion and alkali metal retention. Abstract: The co-combustion of coagulation sludge (CS) and Zhundong coal (ZDc) can simultaneously convert waste to energy and mitigate fouling and slagging problems during circulating fluidized bed (CFB) combustion of ZDc. In order to explore the ash forming characteristics after blending CS with ZDc, the ash melting curve method quantified the real-time ash fusion characteristics, and alkali metal sodium was analyzed. The results revealed that the ash fusion process of ZDc was divided into two stages. During the first stage, shrinkage was caused by the release of Na and the low temperature eutectic of Na2 SO4 and CaSO4 . The aluminosilicates in CS effectively decreased the release of alkali metal sodium and inhibited the low temperature eutectic, so the shrinkage rate of ZDc ash was effectively decreased by blending CS during the first stage. During the second stage of ZDc ash shrinkage, the ash shrinkage temperature decreased and the shrinkage rate increased by blending CS. It was attributed that the iron salts in the blends generated low melting point substances such as SiO2 -Al2 O3 -Fe2 O3 (MP: 1073 ℃), which caused the blends ash to begin to shrink at around 1000 ℃. As the blending ratio increased, iron-bearing minerals formed low temperature eutectic with the minerals previously produced, resulting in the rapid melting of the blends ash at around 1200 °C. In connection with the sodium retention and the ash melting curve, ash formation characteristics were optimized by blending CS with ZDc. The co-combustion of CS and ZDc is suitable for the boiler that operation temperature under 1000 ℃.